Proceedings of the 15th Conference of the European Chapter of The Association for Computational Linguistics: Volume 1 2017
DOI: 10.18653/v1/e17-1065
|View full text |Cite
|
Sign up to set email alerts
|

Noisy-context surprisal as a human sentence processing cost model

Abstract: We use the noisy-channel theory of human sentence comprehension to develop an incremental processing cost model that unifies and extends key features of expectation-based and memory-based models. In this model, which we call noisy-context surprisal, the processing cost of a word is the surprisal of the word given a noisy representation of the preceding context. We show that this model accounts for an outstanding puzzle in sentence comprehension, language-dependent structural forgetting effects (Gibson and Thom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 31 publications
3
61
0
Order By: Relevance
“…There are good theoretical and empirical reasons to believe the HDMI hypothesis is true. The empirically-measured mutual information of words pairs in head-dependent relationships has been found to be greater than various baselines in Futrell and Levy (2017) across languages. Theoretically, it makes sense for word pairs in dependency relationships to have the highest mutual information because mutual information is a measure of the strength of covariance between two variables, and words in dependencies are by definition those word pairs whose covariance is directly constrained by grammatical rules.…”
Section: Dlm As An Approximation To Information Localitymentioning
confidence: 76%
See 1 more Smart Citation
“…There are good theoretical and empirical reasons to believe the HDMI hypothesis is true. The empirically-measured mutual information of words pairs in head-dependent relationships has been found to be greater than various baselines in Futrell and Levy (2017) across languages. Theoretically, it makes sense for word pairs in dependency relationships to have the highest mutual information because mutual information is a measure of the strength of covariance between two variables, and words in dependencies are by definition those word pairs whose covariance is directly constrained by grammatical rules.…”
Section: Dlm As An Approximation To Information Localitymentioning
confidence: 76%
“…3 Lossy-context surprisal and information locality I propose to modify surprisal theory in the manner described in Futrell and Levy (2017). The contents of this section are a simplified exposition of the derivations presented in that paper.…”
Section: Background: Efficient Communication Under Information Procesmentioning
confidence: 99%
“…The interaction between past exposure and working memory is an active area of research. Recent extensions to the surprisal metric (Hale, 2001; Levy, 2008) such as the lossy‐context surprisal (Futrell et al, 2019; Futrell & Levy, 2017) have been shown to predict locality as well as the forgetting effects pattern in English and German. Certain models of working memory that can perform differential resource allocation based on prior experience (Daily, Lovett, & Reder, 2001; Lovett, Daily, & Reder, 2000) also hold promise in accounting for the interaction of limited working memory capacity and past exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Both these factors have been shown to be critical in determining online processing cost (Staub, 2010). And while there are some proposals that have tried to investigate the interaction between the two factors (Campanelli et al, 2018; Demberg, Keller, & Koller, 2013; Futrell & Levy, 2017; Husain & Vasishth, 2014; Husain et al, 2014; Levy & Keller, 2013; Vasishth & Drenhaus, 2011), a formal account of such an interaction over naturalistic data is currently lacking. As we will note later, our work, in fact, points to such an interaction between linguistic exposure and dependency minimization.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Hahn, Degen, Goodman, Jurafsky, and Futrell (2018) show that mutual information contributes to explaining adjective ordering preferences gathered from English speakers; when multiple adjectives are present in a phrase, the adjective with higher mutual information tends to be closer to the noun. Following Futrell and Levy (2017), this could be driven by memory-constrained incremental processing. Placing modifier-noun pairs with high mutual information far apart from one another increases processing effort.…”
Section: Discussionmentioning
confidence: 99%